Moisture-curable polyurethane resin composition, adhesive, and laminate
By using isocyanate-group urethane prepolymer in the wet curing polyurethane resin composition, combining the reaction between the polyester polyol and the polyisocyanate, the problem of difficult to take into account the feel and the adhesiveness after the biomass degree is improved, and a moisture curing polyurethane hot melt resin composition with high biomass degree, excellent feel and adhesiveness is achieved.
Patent Information
- Application Number
- CN202380065541.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-11-29
- Filing Date
- 2023-06-08
- Publication Date
- 2025-04-08
AI Technical Summary
The conventional moisture-curing polyurethane resin composition is difficult to take into account both the feel and the adhesiveness when improving the biomass.
A wet cured polyurethane hot melt resin composition with a biomass degree of 40% or more was prepared by reacting a polyester polyol with a polyisocyanate group.
It realizes the use of biomass raw materials to improve the degree of biomass while maintaining excellent feel and adhesiveness. It is suitable for environmentally friendly moisture-permeable and water-resistant functional clothing.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to a moisture-curable polyurethane resin composition, an adhesive and a laminate. Background Art
[0002] The moisture-permeable and waterproof functional clothing having both moisture permeability and waterproofness is a structure formed by bonding a moisture-permeable film to a fabric using an adhesive. As for the above-mentioned adhesive, a urethane adhesive is generally used from the aspect of good adhesion to both the moisture-permeable film and the fabric. In addition, among the above-mentioned urethane adhesives, the use amount of the moisture-curable polyurethane resin composition as a solvent-free type is gradually increasing due to the recent global solvent emission restrictions and residual solvent restrictions (for example, refer to Patent Document 1).
[0003] On the other hand, as the recent marine plastic problem has attracted much attention, the interest in bio-based resins that aim to get rid of fossil resources has also been increasing, and moisture-curable polyurethane resin compositions are no exception. However, it is pointed out that if the biomass content is increased, the feel and adhesion will decrease, and it is a big issue to balance these properties.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2017-202608 Summary of the invention
[0007] Problems to be solved by the invention
[0008] The problem to be solved by the present invention is to provide a moisture-curable polyurethane resin composition having an increased biomass ratio using a biomass raw material and excellent texture and adhesiveness.
[0009] Means for solving problems
[0010] The present invention provides the following moisture-curable polyurethane hot-melt resin composition, characterized in that it contains a urethane prepolymer (i) having an isocyanate group, wherein the urethane prepolymer (i) is a reaction product of a polyol (A) containing a polyester polyol (a1) and a polyisocyanate (B), and has a biomass degree of 40% or more, and the polyester polyol (a1) uses sebacic acid derived from biomass and diethylene glycol derived from biomass as raw materials.
[0011] The present invention also provides the following adhesive, characterized in that it contains the above-mentioned moisture-curable polyurethane resin composition. The present invention also provides the following laminate, characterized in that it has at least a fabric and a cured product of the above-mentioned moisture-curable polyurethane resin composition.
[0012] Effects of the Invention
[0013] The moisture-curable polyurethane resin composition of the present invention uses a biomass raw material and has a high biomass content, and is an environmentally friendly material. In addition, the moisture-curable polyurethane resin composition of the present invention has both excellent texture and adhesiveness. DETAILED DESCRIPTION
[0014] The moisture-curable polyurethane hot-melt resin composition used in the present invention contains a urethane prepolymer (i) having an isocyanate group, wherein the urethane prepolymer (i) is a reaction product of a polyol (A) containing a specific polyester polyol and a polyisocyanate (B), and has a biomass degree of 40% or more.
[0015] The polyol (A) must contain a polyester polyol (a1) made of biomass-derived sebacic acid and biomass-derived diethylene glycol. By using the specific polyester polyol (a1), the resin film becomes soft and an excellent texture can be obtained even if the biomass content is increased.
[0016] As the biomass-derived sebacic acid, for example, one obtained by a known cracking reaction of vegetable oils such as castor oil with caustic soda can be used. As the sebacic acid, for example, "Bio Seb" manufactured by Toyokuni Oil Co., Ltd. can be obtained as a commercial product.
[0017] As the biomass-derived diethylene glycol, for example, diethylene glycol obtained by a known method using molasses of sugar cane or the like as a raw material can be used. The diethylene glycol is commercially available, for example, as "Bio DEG" manufactured by India Glycols.
[0018] As the raw material of the polyester polyol (a1), in addition to the above raw materials, other polybasic acids and diol compounds may be used in combination.
[0019] As the above-mentioned other polyacids, for example, succinic acid, adipic acid, azelaic acid, dodecanedicarboxylic acid, maleic anhydride, fumaric acid, 1,3-cyclopentanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, and anhydrides thereof can be used. These polyacids can be substances derived from biomass or substances derived from petrochemicals, and can be used alone or in combination of two or more. The usage amount of the above-mentioned sebacic acid derived from biomass in all polyacids is preferably 20 mol % or more, and more preferably 40 mol % or more.
[0020] Examples of the other diol compounds include ethylene glycol, 1,3-propanediol, propylene glycol, 1,4-butanediol, 1,3-butanediol, 1,2-butanediol, 2-methyl-1,3-propanediol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 1,5-hexanediol, 3- Methyl-1,5-pentanediol, 2-methyl-1,8-octanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,8-nonanediol, 2-ethyl-2-butyl-1,3-propanediol, 1,12-dodecanediol, 1,4-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, trimethylolpropane, trimethylolethane, glycerol, ε-caprolactone, etc. These compounds may be biomass-derived substances or petrochemical-derived substances, and may be used alone or in combination of two or more. The amount of the above-mentioned biomass-derived diethylene glycol used in all diol compounds is preferably 20 mol% or more, and more preferably 40 mol% or more.
[0021] The number average molecular weight of the polyester polyol (a1) is preferably 500 to 100,000, more preferably 700 to 50,000, and even more preferably 800 to 10,000, from the viewpoint of obtaining more excellent mechanical strength, texture, and adhesiveness. The number average molecular weight of the polyester polyol (a1) is a value measured by gel permeation chromatography (GPC).
[0022] The polyol (A) must contain the polyester polyol (a1), but may contain other polyols as necessary. The content of the polyester polyol (a1) in the polyol (A) is preferably 20% by mass or more, more preferably 30 to 80% by mass.
[0023] As the above-mentioned other polyols, for example, polyester polyols other than the above-mentioned polyester polyol (a1), polycarbonate polyols, polyether polyols, polybutadiene polyols, polyacrylic polyols, etc. can be used. These polyols can be used alone or in combination of two or more. As for the above-mentioned other polyols, from the aspect of obtaining better mechanical strength and adhesion, it is preferably selected from one or more of the polyester polyols using phthalic acid as a raw material, the polyester polyol using sebacic acid as a raw material, and the polyester polyol using adipic acid as a raw material other than the above-mentioned polyester polyol (a1).
[0024] Examples of the number average molecular weight of the other polyols include 500 to 100,000. The number average molecular weight of the other polyols refers to a value measured by gel permeation chromatography (GPC).
[0025] As the above-mentioned polyisocyanate (B), aromatic polyisocyanates such as polymethylene polyphenyl polyisocyanate, diphenylmethane diisocyanate, carbodiimide-modified diphenylmethane diisocyanate, xylylene diisocyanate, phenylene diisocyanate, toluene diisocyanate, and naphthalene diisocyanate can be used; aliphatic or alicyclic polyisocyanates such as hexamethylene diisocyanate, cyclohexane diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, and tetramethylxylylene diisocyanate can be used. These polyisocyanates can be used alone or in combination of two or more. Among these, aromatic polyisocyanates are preferred, and diphenylmethane diisocyanate is more preferred, from the perspective of obtaining better reactivity, mechanical strength, and adhesion.
[0026] The amount of the polyisocyanate (B) used is preferably in the range of 5 to 40% by mass, more preferably in the range of 10 to 30% by mass, based on the total mass of the raw materials constituting the urethane prepolymer (i).
[0027] The urethane prepolymer (i) is obtained by reacting the polyol (A) and the polyisocyanate (B), and has an isocyanate group that can react with moisture present in the air or in a substrate coated with the moisture-curable polyurethane resin composition to form a crosslinked structure.
[0028] The biomass degree of the hot-melt urethane prepolymer (i) is 40% or more. In the present invention, as described above, by using a specific polyester polyol (a1), excellent feel and adhesion can be obtained even if the biomass degree is high. The biomass degree of the hot-melt urethane prepolymer (i) is more preferably 40% to 70%. It should be noted that the biomass degree of the hot-melt urethane prepolymer (i) represents the total weight ratio of the raw materials derived from biomass used in the production of the hot-melt urethane prepolymer (i) relative to the total weight of the hot-melt urethane prepolymer (i).
[0029] The method for producing the hot-melt urethane prepolymer (i) can be produced, for example, by adding the polyisocyanate (B) to a reaction container containing the polyol (A), and reacting the polyisocyanate (B) under the condition that the isocyanate group of the polyisocyanate (B) is in excess relative to the hydroxyl group of the polyol (A).
[0030] The equivalent ratio (isocyanate group / hydroxyl group) of the isocyanate group of the polyisocyanate (B) to the hydroxyl group of the polyol (A) when producing the hot-melt urethane prepolymer (i) is preferably in the range of 1.2 to 5, and more preferably in the range of 1.5 to 3, from the viewpoint of obtaining better mechanical strength, hand feel and adhesiveness.
[0031] The isocyanate group content (hereinafter referred to as "NCO%") of the hot-melt urethane prepolymer (i) obtained by the above method is preferably in the range of 1.4 to 6, and more preferably in the range of 1.8 to 4.0, from the viewpoint of obtaining more excellent mechanical strength, hand feel and adhesiveness. It should be noted that the NCO% of the hot-melt urethane prepolymer (i) is a value measured by potentiometric titration in accordance with JIS K1603-1:2007.
[0032] The moisture-curable polyurethane hot-melt resin composition used in the present invention contains the above-mentioned urethane prepolymer (i) as an essential component, but other additives may be used as necessary.
[0033] Examples of the other additives include light stabilizers, curing catalysts, tackifiers, plasticizers, stabilizers, fillers, dyes, pigments, fluorescent brighteners, silane coupling agents, waxes, thermoplastic resins, etc. These additives may be used alone or in combination of two or more.
[0034] As described above, the moisture-curable polyurethane resin composition of the present invention uses a biomass raw material and has a high biomass content, and is an environmentally friendly material. In addition, the moisture-curable polyurethane resin composition of the present invention has both excellent texture and adhesiveness.
[0035] Next, the laminated body of the present invention will be described.
[0036] The laminate of the present invention comprises at least a cloth and a cured product of the moisture-curable polyurethane hot-melt resin composition.
[0037] As the above-mentioned fabric, for example, there can be used: fiber substrates such as non-woven fabrics, woven fabrics, and knitted fabrics formed by polyester fibers, polyethylene fibers, nylon fibers, acrylic fibers, polyurethane fibers, acetate fibers, rayon fibers, polylactic acid fibers, cotton, linen, silk, wool, glass fibers, carbon fibers, and blended fibers thereof; materials obtained by impregnating the above-mentioned non-woven fabrics with resins such as polyurethane resins; materials obtained by further providing a porous layer on the above-mentioned non-woven fabrics; resin substrates, etc.
[0038] Examples of a method for applying the moisture-curable polyurethane hot-melt resin composition include methods using a roll coater, a knife coater, a spray coater, a gravure roll coater, a comma coater, a T-die coater, an applicator, a dispenser, and the like.
[0039] After the moisture-curable polyurethane hot-melt resin composition is applied, it can be dried and cured by a known method.
[0040] The thickness of the cured product of the moisture-curable urethane hot-melt resin composition is, for example, in the range of 5 to 500 μm.
[0041] It should be noted that the most preferred embodiment is that the moisture-curable polyurethane hot-melt resin composition of the present invention is used as an adhesive for moisture-permeable and waterproof functional clothing. In this case, the moisture-curable polyurethane hot-melt resin composition is preferably intermittently coated by a gravure roll coater or a dispenser, and the fabric is bonded to a known moisture-permeable film. In this case, the thickness of the cured product of the moisture-curable polyurethane hot-melt resin composition is, for example, in the range of 5 to 300 μm.
[0042] Example
[0043] Hereinafter, the present invention will be described in more detail using examples.
[0044] [Example 1]
[0045] In a four-necked flask equipped with a thermometer, a stirrer, an inert gas inlet and a reflux condenser, 112 parts by mass of a polyester polyol (a reaction product of sebacic acid derived from biomass ("Bio Seb" manufactured by Toyokuni Oil Co., Ltd.) and diethylene glycol derived from biomass ("Bio DEG" manufactured by India Glycols Co., Ltd., number average molecular weight: 2,000, hereinafter referred to as "Bio PEs (1)") and 112 parts by mass of a polyester polyol (a reaction product of sebacic acid derived from biomass ("Bio Seb" manufactured by Toyokuni Oil Co., Ltd.) and 1,6-hexanediol derived from petrochemicals, number average molecular weight: 3,500, hereinafter referred to as "Bio PEs (2)") 31 parts by mass, polyester polyol (reaction product of petrochemical 1,6-hexanediol and petrochemical phthalic acid, number average molecular weight: 2,000, hereinafter referred to as "other PEs (1)") 41 parts by mass, polyester polyol (reaction product of petrochemical neopentyl glycol and petrochemical phthalic acid, number average molecular weight: 1,000, hereinafter referred to as "other PEs (2)") 20 parts by mass were dried under reduced pressure at 110°C to dehydrate the water content to 0.05% by mass or less. Then, after cooling to 60°C, 45.9 parts by mass of diphenylmethane diisocyanate (hereinafter referred to as "MDI") was added, the temperature was raised to 110°C, and the reaction was carried out for 2 hours until the isocyanate group content became constant, thereby obtaining a urethane prepolymer (i-1), and a moisture-curable polyurethane hot-melt resin composition was prepared.
[0046] [Example 2]
[0047] In a four-necked flask equipped with a thermometer, a stirrer, an inert gas inlet and a reflux condenser, 139 parts by mass of BioPEs (1) and 59 parts by mass of other PEs (2) were placed, and dried under reduced pressure at 110° C. to dehydrate the mixture until the moisture content became 0.05% by mass or less. Then, after cooling to 60° C., 56.7 parts by mass of MDI was added, the temperature was raised to 110° C., and the mixture was reacted for 2 hours until the isocyanate group content became constant, thereby obtaining a urethane prepolymer (i-2) and preparing a moisture-curable polyurethane hot-melt resin composition.
[0048] [Example 3]
[0049] In a four-necked flask equipped with a thermometer, a stirrer, an inert gas inlet and a reflux condenser, 136 parts by mass of BioPEs (1), 136 parts by mass of Bio PEs (2) and 68 parts by mass of other PEs (2) were placed and dried under reduced pressure at 110° C. to dehydrate the mixture until the moisture content became 0.05% by mass or less. Then, after cooling to 60° C., 93.2 parts by mass of MDI was added, the temperature was raised to 110° C., and the mixture was reacted for 2 hours until the isocyanate group content became constant, thereby obtaining a urethane prepolymer (i-3) and preparing a moisture-curable polyurethane hot-melt resin composition.
[0050] [Example 4]
[0051] In a four-necked flask equipped with a thermometer, a stirrer, an inert gas inlet and a reflux condenser, 61 parts by mass of BioPEs (1), 9 parts by mass of other PEs (1) and 17 parts by mass of other PEs (2) were placed and dried under reduced pressure at 110° C. to dehydrate the mixture until the moisture content was 0.05% by mass or less. Then, after cooling to 60° C., 25.9 parts by mass of MDI was added, the temperature was raised to 110° C., and the mixture was reacted for 2 hours until the isocyanate group content became constant, thereby obtaining a urethane prepolymer (i-4) and preparing a moisture-curable polyurethane hot-melt resin composition.
[0052] [Example 5]
[0053] In a four-necked flask equipped with a thermometer, a stirrer, an inert gas inlet and a reflux condenser, 64 parts by mass of BioPEs (1), 26 parts by mass of Bio PEs (2), 13 parts by mass of other PEs (1) and 13 parts by mass of other PEs (2) were placed and dried under reduced pressure at 110° C. to dehydrate the mixture until the moisture content became 0.05% by mass or less. Subsequently, the mixture was cooled to 60° C., 29.1 parts by mass of MDI was added, the temperature was raised to 110° C., and the mixture was reacted for 2 hours until the isocyanate group content became constant, thereby obtaining a urethane prepolymer (i-5) and preparing a moisture-curable polyurethane hot-melt resin composition.
[0054] [Example 6]
[0055] In a four-necked flask equipped with a thermometer, a stirrer, an inert gas inlet and a reflux condenser, 192 parts by mass of BioPEs (1), 32 parts by mass of Bio PEs (2), 48 parts by mass of other PEs (1) and 48 parts by mass of other PEs (2) were placed and dried under reduced pressure at 110° C. to dehydrate the mixture until the moisture content became 0.05% by mass or less. Subsequently, the mixture was cooled to 60° C., 80 parts by mass of MDI was added, the temperature was raised to 110° C., and the mixture was reacted for 2 hours until the isocyanate group content became constant, thereby obtaining a urethane prepolymer (i-6) and preparing a moisture-curable polyurethane hot-melt resin composition.
[0056] [Example 7]
[0057] In a four-necked flask equipped with a thermometer, a stirrer, an inert gas inlet and a reflux condenser, 49 parts by mass of BioPEs (1), 29 parts by mass of Bio PEs (2) and 19 parts by mass of other PEs (1) were placed and dried under reduced pressure at 110° C. to dehydrate the mixture until the moisture content was 0.05% by mass or less. Then, after cooling to 60° C., 20.3 parts by mass of MDI was added, the temperature was raised to 110° C., and the mixture was reacted for 2 hours until the isocyanate group content became constant, thereby obtaining a urethane prepolymer (i-7) and preparing a moisture-curable polyurethane hot-melt resin composition.
[0058] [Comparative Example 1]
[0059] In a four-necked flask equipped with a thermometer, a stirrer, an inert gas inlet and a reflux condenser, 50 parts by mass of BioPEs (2), 84 parts by mass of other PEs (1) and 33 parts by mass of other PEs (2) were placed and dried under reduced pressure at 110° C. to dehydrate the mixture until the moisture content became 0.05% by mass or less. Then, after cooling to 60° C., 38.4 parts by mass of MDI was added, the temperature was raised to 110° C., and the mixture was reacted for 2 hours until the isocyanate group content became constant, thereby obtaining a urethane prepolymer (iR-1) and preparing a moisture-curable polyurethane hot-melt resin composition.
[0060] [Comparative Example 2]
[0061] In a four-necked flask equipped with a thermometer, a stirrer, an inert gas inlet and a reflux condenser, 18 parts by mass of BioPEs (1), 72 parts by mass of Bio PEs (2), 54 parts by mass of other PEs (1) and 36 parts by mass of other PEs (2) were placed and dried under reduced pressure at 110° C. to dehydrate the mixture until the moisture content became 0.05% by mass or less. Subsequently, the mixture was cooled to 60° C., 36.9 parts by mass of MDI was added, the temperature was raised to 110° C., and the mixture was reacted for 2 hours until the isocyanate group content became constant, thereby obtaining a urethane prepolymer (iR-2) and preparing a moisture-curable polyurethane hot-melt resin composition.
[0062] [Method for measuring number average molecular weight]
[0063] The number average molecular weight of the polyol used in Examples and Comparative Examples refers to a value measured by gel permeation chromatography (GPC) under the following conditions.
[0064] Measuring device: High-speed GPC device (Tosoh Corporation "HLC-8220GPC")
[0065] Column: The following columns manufactured by Tosoh Corporation were connected in series and used.
[0066] "TSKgel G5000" (7.8 mmI.D. × 30 cm) × 1
[0067] "TSKgel G4000" (7.8 mm I.D. × 30 cm) × 1 piece
[0068] "TSKgel G3000" (7.8 mmI.D. × 30 cm) × 1
[0069] "TSKgel G2000" (7.8 mm I.D. × 30 cm) × 1 piece
[0070] Detector: RI (differential refractometer)
[0071] Column temperature: 40°C
[0072] Eluent: Tetrahydrofuran (THF)
[0073] Flow rate: 1.0 mL / min
[0074] Injection volume: 100 μL (sample concentration is 0.4 mass% tetrahydrofuran solution)
[0075] Standard samples: The following standard polystyrene was used to prepare a calibration curve.
[0076] (Standard Polystyrene)
[0077] "TSKgel Standard Polystyrene A-500" manufactured by Tosoh Corporation
[0078] "TSKgel Standard Polystyrene A-1000" manufactured by Tosoh Corporation
[0079] "TSKgel Standard Polystyrene A-2500" manufactured by Tosoh Corporation
[0080] "TSKgel Standard Polystyrene A-5000" manufactured by Tosoh Corporation
[0081] "TSKgel Standard Polystyrene F-1" manufactured by Tosoh Corporation
[0082] "TSKgel Standard Polystyrene F-2" manufactured by Tosoh Corporation
[0083] "TSKgel Standard Polystyrene F-4" manufactured by Tosoh Corporation
[0084] "TSKgel Standard Polystyrene F-10" manufactured by Tosoh Corporation
[0085] "TSKgel Standard Polystyrene F-20" manufactured by Tosoh Corporation
[0086] "TSKgel Standard Polystyrene F-40" manufactured by Tosoh Corporation
[0087] "TSKgel Standard Polystyrene F-80" manufactured by Tosoh Corporation
[0088] "TSKgel Standard Polystyrene F-128" manufactured by Tosoh Corporation
[0089] "TSKgel Standard Polystyrene F-288" manufactured by Tosoh Corporation
[0090] "TSKgel Standard Polystyrene F-550" manufactured by Tosoh Corporation
[0091] [Evaluation method of adhesiveness]
[0092] In a high temperature and high humidity room adjusted to a temperature of 23°C and a humidity of 50±5%, a moisture curable polyurethane hot melt resin composition obtained in the examples and comparative examples, which had been melted at 100°C, was coated on a moisture permeable film (VENTEX manufactured by Kahei Co., Ltd.) using a gravure coater to a density of 17.5±5 g / m 2The processed cloth was obtained by intermittent coating in a manner of 23°C and laminating the polyester cloth for 24 hours at a temperature of 23°C and a humidity of 50±5%. The processed cloth was cut into 1 inch width, and the peel strength was measured using Tensilon (Tensilon Universal Testing Machine "RTC-1210A" manufactured by Orientec Co., Ltd.) at a crosshead speed of 200 mm / min, and evaluated as follows.
[0093] “○”: 8 N / cm or more
[0094] “×”: less than 8 N / cm
[0095] [Evaluation method of hand feel]
[0096] The processed cloth obtained in the above [Evaluation method of adhesion] was cut into 1 inch width and 8 cm length, and the test piece was folded in half using a precision universal testing machine ("Autograph AG-1" manufactured by Shimadzu Corporation), and the folded part was attached so that the folded part with a length of 5 cm had an arc and protruded toward the upper part of the clamping fixture. The stress when the flat indenter was pressed at a test speed of 10 mm / min and displaced 5 mm was measured, and evaluated as follows.
[0097] “○”: 100 mN or less
[0098] “×”: more than 100 mN
[0099] [Table 1]
[0100]
[0101] [Table 2]
[0102]
[0103] It is found that the moisture-curable polyurethane hot-melt resin composition of the present invention has a high biomass content and has excellent adhesiveness and texture.
[0104] On the other hand, in Comparative Example 1, which is a method in which the polyester polyol (a1) was not used, the adhesiveness and the texture were poor.
[0105] Comparative Example 2 is an embodiment in which only a small amount of polyester polyol (a1) is used and the biomass degree is below the range specified in the present invention, and the adhesiveness and texture are poor.
Claims
1. A moisture-curable polyurethane hot-melt resin composition, characterized in that: The invention relates to a urethane prepolymer (i) having an isocyanate group, wherein the urethane prepolymer (i) is a reaction product of a polyol (A) including a polyester polyol (a1) and a polyisocyanate (B), and has a biomass degree of 40% or more, wherein the polyester polyol (a1) uses sebacic acid derived from biomass and diethylene glycol derived from biomass as raw materials.
2. An adhesive, characterized in that: A moisture-curable polyurethane resin composition according to claim 1.
3. A laminated body, characterized in that: A cured product of the moisture-curable polyurethane resin composition according to claim 1 and at least a cloth.
Citation Information
Patent Citations
Sheet material
JP2017202608A